2021
DOI: 10.1007/s10151-021-02471-2
|View full text |Cite
|
Sign up to set email alerts
|

Right hemicolectomy with complete mesocolic excision is safe, leads to an increased lymph node yield and to increased survival: results of a systematic review and meta-analysis

Abstract: Background The introduction of complete mesocolic excision (CME) for right colon cancer has raised an important discussion in relation to the extent of colic and mesenteric resection, and the impact this may have on lymph node yield. As uncertainty remains regarding the usefulness of and indications for right hemicolectomy with CME and the benefits of CME compared with a traditional approach, the purpose of this meta-analysis is to compare the two procedures in terms of safety, lymph node yield a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 58 publications
1
29
0
4
Order By: Relevance
“…It did result in a substantial rise in the lymph nodes collected number, which in turn decreased the LNR, it is strongly connected to DFS (17) . Our findings concur with those of research that shows that right hemicolectomy with CME produces more lymph nodes than conventional surgery in terms of oncologic results (MD 7.05, 95 percent CI 4.06-10.04) (18) . As was already mentioned, adhering to the recommendations of a combined CME and CVL will impacts the quantity of lymph nodes gathered, cover a sizable drainage area, like the CVL area, and have central or apical lymph nodes that are skipped in a classic dissection, potentially under-staging the cancer from phase III to phase II, such skipped micro metastases may result in a future local recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…It did result in a substantial rise in the lymph nodes collected number, which in turn decreased the LNR, it is strongly connected to DFS (17) . Our findings concur with those of research that shows that right hemicolectomy with CME produces more lymph nodes than conventional surgery in terms of oncologic results (MD 7.05, 95 percent CI 4.06-10.04) (18) . As was already mentioned, adhering to the recommendations of a combined CME and CVL will impacts the quantity of lymph nodes gathered, cover a sizable drainage area, like the CVL area, and have central or apical lymph nodes that are skipped in a classic dissection, potentially under-staging the cancer from phase III to phase II, such skipped micro metastases may result in a future local recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…According to the latest study, we believe that CME has not proved inferior to traditional surgery in terms of feasibility and safety. And with the expansion of future research samples, this conclusion will be evaluated more accurately [ 34 ]. The current study constructed a novel nomogram based on the findings of multivariate logistic regression analysis, including male sex, open surgery, operative time, and anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of colon cancer surgery has been completed and standardized since Hohenberger et al [8] proposed complete mesocolic excision (CME) by combining lymphatic drainage with mesocolic plane dissection, in which the embryological mesocolon, from the viscera to the parietal planes, is removed horizontally and the main artery pedicle is ligated at the root in the vertical direction. Recent studies showed that CME could eliminate tumour tissue by removing the entire relevant mesentery, thereby reducing local recurrence and improving survival significantly [9–13]. However, most studies regarding AC were performed at a time when CME was not proposed and generalized [14].…”
Section: Introductionmentioning
confidence: 99%
“…drainage with mesocolic plane dissection, in which the embryological mesocolon, from the viscera to the parietal planes, is removed horizontally and the main artery pedicle is ligated at the root in the vertical direction. Recent studies showed that CME could eliminate tumour tissue by removing the entire relevant mesentery, thereby reducing local recurrence and improving survival significantly [9][10][11][12][13].…”
mentioning
confidence: 99%